3D silhouette rendering algorithms using vectorisation technique from Kedah topography map - Che Mat, Ruzinoor; Nordin, Norani (Universiti Teknologi Malaysia, 2004)
Most of the applications in real world today are more toward non-photorealistic rather than photorealistic. Slihouette Rendering Algorithms is one of the technique that important in creating non-photorealistic image. It has been successful used in various applications such as game engine, communicating shape, cartoon rendering and 3D terrain visualization. This paper explores how silhouette rendering algorithms could be created using a data that have been extracted from Kedah topography map. Contour data from a topography map are convert from raster to vector (vectorisation) in order to create a grid terrain Digital Elevation Model (DEM) data. The vectorisation software has been used for producing these data. The data then convert into the format that suitable for existing 3D silhouette software. The results produced compatible terrain images of Sik District, Kedah that are closer to human drawn illustration and look like an artistic style.